Scavenging beetles control the temporal response of soil communities to carrion decomposition. (21st June 2021) - Ilardi, Marco O.; Cotter, Sheena C.; Hammer, Edith C.; Riddell, Gillian; Caruso, Tancredi
Abstract: Carrion is a frequent but overlooked source of nutrients to the soil. The decomposition of carrion is accelerated by invertebrate scavengers, but the impact of the scavengers on below‐ground biota and its functions is scarcely known. We conducted a laboratory experiment to investigate the effects of the burying beetle Nicrophorus vespilloides on the soil community of a temperate broadleaved forest. We assembled microcosms from soil collected from an oak woodland and treated them with mouse Mus musculus carcasses and mating pairs of burying beetles (♀+♂) in a factorial design with control soils. We sampled independent replicates over time to investigate how the beetles affect soil microarthropods and microbial biomass (bacteria and fungi) in relation to soil pH and organic matter content. The beetle treatment initially reduced the total microbial biomass and abundance of major groups of microarthropods relative to the control soil. At the same time, organic matter increased in the beetle treatment and then dropped to the pre‐beetle level (i.e. soil baseline) at the end of the beetle breeding cycle (2 weeks). The rapid temporal changes in organic matter were mimicked by the relative abundances of the dominant microarthropod groups, with Oribatida relatively more abundant than Collembola and predaceous mites in the beetle treatment. The overall final effect of the beetle (relative to the laboratory control) on microarthropods was negative but the beetle kept these variables within the levels observed for freshly collected soil (baseline), while the final effect on pH was positive, and most likely driven by the surplus of nutrients from the carcass and biochemical changes triggered by the decomposition process. In nature, scavenging invertebrates are widespread. Our study demonstrates that beetles breeding in carcasses regulate the dynamics of key components of the soil food web, including microbial biomass, changes in the relative abundances of dominant microarthropods and soil organic matter and pH. Given the abundance of these beetles in nature, the study implies that the distribution of these beetles is a key driver of variation in soil nutrient cycling in woodlands. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.